Adjuvant Temozolomide for the Treatment of Glioblastoma: A Meta-analysis of Randomized Controlled Studies. Issue 4 (July 2021) - Zhao, Yan; Wu, Jie; Shi, Lunbo
Abstract : Introduction: The efficacy of adjuvant temozolomide to radiotherapy for glioblastoma remained elusive. This meta-analysis aimed to explore the influence of radiotherapy plus adjuvant temozolomide on the efficacy and safety for glioblastoma. Methods: We have searched several databases including PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through November 2020 and included randomized controlled trials assessing the efficacy and safety of adjuvant temozolomide to radiotherapy for glioblastoma. Results: Seven randomized controlled trials and 1900 patients were included in the meta-analysis. Overall, compared with radiotherapy for glioblastoma, adjuvant temozolomide was associated with significantly increased survival rate [odds ratio (OR), 4.04; 95% confidence interval (CI), 2.61–6.24; P < 0.00001], median progression-free survival (mean difference, 0.55; 95% CI, 0.03–1.07; P = 0.04), and hematological complications (OR, 4.12; 95% CI, 1.43–11.88; P = 0.009), but revealed no remarkable influence on adverse events (OR, 0.87; 95% CI, 0.36–2.09; P = 0.75) or serious adverse events (OR, 2.20; 95% CI, 0.55–8.70; P = 0.26). Conclusions: Adjuvant temozolomide in combination with radiotherapy may improve the treatment efficacy for glioblastoma.